A multicenter review of infusion-related reactions to daratumumab for relapsed multiple myeloma in the real world setting. (June 2021) - Geirnaert, Marc; Howarth, Jacy; Martin, Kristen; Ricard, Chad; Streilein, Scott; Wasney, Danica; Dao, Vi; Kotb, Rami; Rimmer, Emily; Minuk, Leonard
Background: Daratumumab is used in the treatment of relapsed multiple myeloma. Daratumumab infusion-related reactions can occur with the highest incidence on the first infusion. Methods: A retrospective review of all daratumumab infusions used as part of the DVd and DRd regimens for relapsed multiple myeloma was undertaken. The review of infusion-related reactions was conducted by reviewing the treatment room nursing note on the days that daratumumab was administered. If the patient experienced an infusion-related reaction, then the data captured included if the full dose was administered. Results: Daratumumab infusion-related reactions occurred most frequently on the first dose. The rates of infusion-related reactions using a split dose approach for daratumumab administration were lower than that reported in clinical trials. All of the infusion-related reactions were managed with appropriate interventions in the outpatient setting. The adoption of rapid infusion daratumumab beginning with cycle 2 of DVd and DRd was well tolerated. Conclusions: Our experience of daratumumab infusions using a split dose approach was associated with an infusion-related reaction rate in 28% of patients on cycle 1, day 1 of DVd and DRd regimens. All patients were able to complete full doses of daratumumab by utilizing split dose. The rates of daratumumab infusion-related reactions are highest on the first infusion. In addition, our adoption of rapid infusion daratumumab was safe.